PSPICE and MATLAB for electronics : an integrated approach - Attia, John Okyere (VLSI circuits series., 2010)
Used collectively, PSPICE and MATLAB[registered] are unsurpassed for circuit modeling and data analysis. This title illustrates how to use the strong features of PSPICE and the powerful functions of MATLAB for electronic circuit analysis.